An Analysis of the Google Form Application as a School Final Examination Platform: Case Study of Islamic Religious Education Subjects at SMAN 74 Jakarta - Ramadhan, Satria Putra; Lismawati, Lismawati (Jurnal Ilmiah Mandala Education (JIME), 2024)
Learning evaluation is an assessment process carried out systematically and continuously on students to determine learning outcomes. In addition to the role of teachers who are very important in increasing students' interest in learning, learning media is also equally important so that students feel comfortable and receive knowledge easily. This study aims to determine the extent of the implementation of the final exam at SMAN 74 using the Google form platform in Islamic Religious Education (PAI) Lessons. The research method used is a quantitative description method with qualitative research types, case studies, and research subjects of 2 class XI teachers of SMAN 74 Jakarta. The instruments used include observation, interviews, documentation, and field recording. Data analysis techniques are carried out according to scientific procedures for qualitative research case studies. The results showed that not all exams or evaluations using the Google form application were successful in improving students' understanding and grades, this was due to various factors both internal and external. However, teachers need to try their best to overcome these obstacles so that all students can take the final school exams well